Investigation of Anaplasma marginale Seroprevalence in a Traditionally Managed Large California Beef Herd - Thomas R. Tucker; Sharif S. Aly; John Maas; Josh S. Davy; Janet E. Foley (Veterinary Medicine International)
Recent observations by stakeholders suggested that ecosystem changes may be driving an increased incidence of bovine erythrocytic anaplasmosis, resulting in a reemerging cattle disease in California. The objective of this prospective cohort study was to estimate the incidence of Anaplasma marginale infection using seroconversion in a northern California beef cattle herd. A total of 143 Black Angus cattle (106 prebreeding heifers and 37 cows) were enrolled in the study. Serum samples were collected to determine Anaplasma marginale seroprevalence using a commercially available competitive enzyme-linked immunosorbent assay test kit. Repeat sampling was performed in seronegative animals to determine the incidence density rate from March through September (2013). Seroprevalence of heifers was significantly lower than that of cows at the beginning of the study (P<0.001) but not at study completion (P=0.075). Incidence density rate of Anaplasma marginale infection was 8.17 (95% confidence interval: 6.04, 10.81) cases per 1000 cow-days during the study period. Study cattle became Anaplasma marginale seropositive and likely carriers protected from severe clinical disease that might have occurred had they been first infected as mature adults. No evidence was found within this herd to suggest increased risk for clinical bovine erythrocytic anaplasmosis.